Lesions of sarcoidosis : a problem solving approach - Sharma, Om P.; Mihailovic-Vucinic, Violeta; Baughman, Robert P. (New Delhi : Jaypee-Highligts Medical Publishers, 2014)
Part of the Clinical Focus Series, this book provides trainees with an overview of lesions of sarcoidosis. Begins with introduction and guidance on recognising pulmonary granulomas, then depth coverage of numerous common lesions, describing their history, clinical features, differential diagnosis and treatment.
Part of the Clinical Focus Series, this book provides trainees with an overview of lesions of sarcoidosis. Begins with introduction and guidance on recognising pulmonary granulomas, then depth coverage of numerous common lesions, describing their history, clinical features, differential diagnosis and treatment.
CONTENTS 1. Sarcoidosis A Worldwide Disease 2. A Clinical Approach to Recognizing Pulmonary Granulomas 3. Fatigue in Sarcoidosis 4. Cough in Sarcoidosis; Chapter 5. Dyspnea in Sarcoidosis y otros 27 capítulos más